STUDI FLUORESENS FIKOSIANIN DARI MIKROALGA Spirulina platensis DAN FOTOSENSITISASI NANOPARTIKEL TiO2 ANATASE - Supu Idawati (Jurnal Biofisika, 2013)
The electron injection (photosensitization) between titanium oxide (TiO2) nanoparticle and  phycocyanin  has  been studied.  The  TiO2  nanoparticle was  synthesized  by sol gel  method  using  TiCl4  as  titanium  source  and  H2SO4  as  hydrolysis  phase.  XRD pattern  showed  crystalline  phase  (anatase  phase)  when  annealed  at  temperature 600oC. According to the XRD pattern and SEM images, crystal  size and particle size were  49.30  nm  and  44.91  nm,  respectively.  The  optical  measurement  of TiO2/phycocyanin  hybrid  film  carried  out  using  UV-Vis  spectrophotometer. Phycocyanin  has  structure  which  conjugated  double  bonds,  such  as  carboxyl  (-COOH)  group  can  be  explored  its  potential  as  anchoring  group  to  TiO2 semiconductor surface.  The strongest  absorption peak  of phycocyanin observed at wavelength  619.36  nm  with  relaxation  energy  2.945  eV.  Moreover,  the  maximum emission  spectrum  as  observed  at  wavelength  708.55  nm  and  relaxation  energy 2.793 eV.  It was one of the  characteristic  pigment  suitable used  as a  sensitizer  in solar cell. Additional of phycoyanin increased absorption spectrum from UV to visible region and indicated well efficiency in solar cell application like DSSC.